Management of Sudden Sensorineural Hearing Loss in Multiple Sclerosis: A Comprehensive Case Report of a Patient with Bilateral Loss and Literature Review - Ikhee Kim; Hantai Kim (Life, 2024)
In multiple sclerosis (MS), the occurrence of sudden sensorineural hearing loss (SSNHL) is considered rare, with reported cases predominantly being unilateral. Bilateral cases are even rarer. Here, we report a case of bilateral SSNHL in a 20-year-old male diagnosed with MS. The patient, undergoing corticosteroid therapy for the management of MS, additionally received an intratympanic dexamethasone injection; however, it could not achieve significant improvement. Subsequently, the systemic dosage was increased for one week, resulting in substantial hearing improvement in both ears after three months. A review of MS-related SSNHL cases from 1987 to 2022 revealed 39 ears in the literature, with only five ears showing no hearing recovery. A remarkable 87.2% exhibited restored hearing, presenting a more favorable prognosis compared with idiopathic SSNHL. Although there were slight variations in administration methods and duration, all documented treatment approaches involve systemic corticosteroids. In some instances, SSNHL manifested as the initial symptom of MS. When SSNHL occurs in MS, auditory brainstem response (ABR) tests may reveal prolonged abnormalities, making ABR testing effective in cases where MS is suspected following SSNHL. In conclusion, the treatment of MS-related SSNHL appears appropriate with systemic corticosteroids, showing a significantly superior prognosis compared with idiopathic SSNHL.